Unlocking Kudu-Laos: Transforming Indonesia's Ethnic Herbal Drink with SMEs Development Support - Setiawan, Vendra; Krisnawan, Alfian Hendra; Nugroho, JL Eko; Wahyudi, Eko Setyo; Alang, Cindy Anastasia; Simamora, Monica Celia (LP2M INSURI Ponorogo, 2025)
This community service set out to improve the sustainability of Mr. Lamiran's Jamu Kudu-Laos SME through improved product quality, diversification, and marketing strategies. This study uses the Participatory Action Research (PAR) method to address key challenges by training on hygiene and measuring tools for consistent production, developing powdered jamu to extend shelf life, and redesigning packaging for better market appeal. An Increase in understanding of product diversification showed a 50% increase and a 16.7% increase in production techniques. Interestingly, hygiene practices and the use of measuring instruments were consistently applied. 30% of sales increase within three months of the training further demonstrated the program's impact. SWOT analysis highlighted product diversification as a key strength, while low public trust in herbal products remains challenging. Further research on evidence-based marketing, such as antioxidant activity testing, is recommended to increase consumer confidence. The finding indicates that community service supports the sustainability of Mr. Lamiran’s Jamu Kudu-Laos SME